2022
DOI: 10.1021/acs.inorgchem.2c01145
|View full text |Cite
|
Sign up to set email alerts
|

So Close, Yet so Different: How One Donor Atom Changes Significantly the Photophysical Properties of Mononuclear Cu(I) Complexes

Abstract: The manipulation of the photophysical properties of molecular emitters can be realized by composing the close environment of the metal center with the “heavier pnictogen atom” effect. Replacing a nitrogen atom with a heavier phosphorus atom in otherwise isostructural molecular systems results in a significant change of the photophysical parameters. Herein, we report on the synthesis of four pairs of novel phosphinine-based and isostructural diimine-based Cu­(I) complexes, which feature peculiar photophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…In addition to the steric effect brought by substituents close to copper, remote substituents have also been shown to have an effect, as highlighted by the studies of a series of heteroleptic complexes built upon Xantphos ( PP 4 ) as the diphosphine and various substituted 5-phenyl-bipyridines and a series of heteroleptic complexes built upon DPEphos ( PP 1 ) or Xantphos ( PP 4 ) in combination with 2,2′-bipyridines possessing one or two unconjugated alkenes at their 6 and 6′ positions . Moreover, replacing a nitrogen atom in the diimine ligand by a phosphorous atom significantly changes the photophysical properties of the resulting complexes, as nicely highlighted in a systematic study recently reported . Four-coordinate copper­(I) complexes bearing neutral diimine and anionic β-diketiminate ligands have been shown to be promising due to an easy tuning of the HOMO−LUMO gap and the corresponding charge-transfer absorption band that can be independently and systematically controlled via ligand modification .…”
mentioning
confidence: 99%
“…In addition to the steric effect brought by substituents close to copper, remote substituents have also been shown to have an effect, as highlighted by the studies of a series of heteroleptic complexes built upon Xantphos ( PP 4 ) as the diphosphine and various substituted 5-phenyl-bipyridines and a series of heteroleptic complexes built upon DPEphos ( PP 1 ) or Xantphos ( PP 4 ) in combination with 2,2′-bipyridines possessing one or two unconjugated alkenes at their 6 and 6′ positions . Moreover, replacing a nitrogen atom in the diimine ligand by a phosphorous atom significantly changes the photophysical properties of the resulting complexes, as nicely highlighted in a systematic study recently reported . Four-coordinate copper­(I) complexes bearing neutral diimine and anionic β-diketiminate ligands have been shown to be promising due to an easy tuning of the HOMO−LUMO gap and the corresponding charge-transfer absorption band that can be independently and systematically controlled via ligand modification .…”
mentioning
confidence: 99%
“…The phenomenon of the system stabilization via supramolecular chelation can be utilized for the synthesis of highly labile species such as air-sensitive metal-organic compounds, particularly, copper­(I) derivatives. Since Cu I -based metal complexes are widely used in catalysis of important chemical transformations, construction of luminescent materials, and design of antitumor agents, , novel approaches improving their stability are in high demand.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a diverse range of C-, N-, P-, As-, and S-based ligands are utilized for the preparation of emissive Cu(I) complexes. [1][2][3][4][5][6][7][8][9][10][11][12][24][25][26][27][28][29][30] Among them, N-heteroarylphosphines (foremost, pyridylphosphines) have gained great attention as very efficient and versatile 1,3-P,N-ligands for the construction of Cu(I) emitters. [30][31][32][33][34] The presence of π-acceptor N-heterocyclic units in these ligands ensures the generation of MLCT excited states, and coordination of a strong σ-donating P atom to Cu(I) additionally facilitates the MLCT effect and enhances the structural stability.…”
Section: Introductionmentioning
confidence: 99%